THE CURRENT TEACHER EVALUATION SYSTEM IS THE KPI SYSTEM. (Multidisciplinary Journal of Science and Technology, 2024)
The Key Performance Indicator (KPI) system is widely used in various sectors, including education, to assess and measure the performance of employees. In the context of teaching, the KPI system offers a structured approach to evaluate the effectiveness of teachers, ensuring that educational standards are maintained and enhanced. This system focuses on quantifiable indicators that reflect the teacher's contribution to students' academic progress, professional development, and overall performance. The KPI system in education not only aims to monitor teachers' individual achievements but also supports institutional development by providing data-driven insights. This paper explores the current use of the KPI system in assessing teachers, discusses its benefits and challenges, and suggests improvements for its effective implementation in educational institutions. By evaluating teachers through KPIs, schools and universities can align educational goals with performance expectations and improve the quality of teaching.